The needs of persons with lupus and health care providers: a qualitative study aimed toward the development of the Lupus Interactive Navigator™. (February 2014) - Neville, C; Costa, D Da; Mill, C; Rochon, M; Aviña-Zubieta, JA; Pineau, CA; Eng, D; Fortin, PR
Objective: Systemic lupus erythematosus is an inflammatory autoimmune disease associated with high morbidity and unacceptable mortality. A major challenge for persons with lupus is coping with their illness and complex care. Our objective was to identify the informational and resource needs of persons with lupus, rheumatologists, and allied health professionals treating lupus. Our findings will be applied toward the development of an innovative web-based technology, the Lupus Interactive Navigator (LIN™), to facilitate and support engagement and self-management for persons with lupus. Methods: Eight focus groups were conducted: four groups of persons with lupus ( n = 29), three groups of rheumatologists ( n = 20), and one group of allied health professionals ( n = 8). The groups were held in British Columbia, Ontario, and Quebec. All sessions were audio-recorded and transcribed verbatim. Qualitative analysis was performed using grounded theory. The transcripts were reviewed independently and coded by the moderator and co-moderator using 1) qualitative data analysis software developed by Provalis Research, Montreal, Canada, and 2) manual coding. Results: Four main themes emerged: 1) specific information and resource needs; 2) barriers to engagement in health care; 3) facilitators of engagement in health care; and 4) tools identified as helpful for the self-management of lupus. Conclusion: These findings will help guide the scope of LIN™ with relevant information topics and specific tools that will be most helpful to the diverse needs of persons with lupus and their health care providers.